2012
DOI: 10.1016/j.jhealeco.2011.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Does health insurance coverage lead to better health and educational outcomes? Evidence from rural China

Abstract: Using the 2006 China Agricultural Census (CAC), we examine whether the introduction of the New Cooperative Medical System (NCMS) has affected child mortality, maternal mortality, and school enrollment of 6-16year olds. Our data cover 5.9 million people living in eight low-income rural counties, of which four adopted the NCMS by 2006 and four did not adopt it until 2007. Raw data suggest that enrolling in the NCMS is associated with better school enrollment and lower mortality of young children and pregnant wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
115
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(125 citation statements)
references
References 25 publications
8
115
2
Order By: Relevance
“…On quality, earlier studies using data on the elderly show a decline in mortality rates (25,27) and an increase in longevity (25) associated with insurance reform, but studies in later years that control for endogenous insurance enrollment show no impact of Rural Resident Insurance on mortality measured for the general, maternal, and child populations (11,12). Even though enrollees of the Urban Employee Insurance program had the highest levels of self-reported health across multiple household surveys, the introduction of insurance did not have a positive impact on health status (26,41).…”
Section: Access and Utilizationmentioning
confidence: 97%
“…On quality, earlier studies using data on the elderly show a decline in mortality rates (25,27) and an increase in longevity (25) associated with insurance reform, but studies in later years that control for endogenous insurance enrollment show no impact of Rural Resident Insurance on mortality measured for the general, maternal, and child populations (11,12). Even though enrollees of the Urban Employee Insurance program had the highest levels of self-reported health across multiple household surveys, the introduction of insurance did not have a positive impact on health status (26,41).…”
Section: Access and Utilizationmentioning
confidence: 97%
“…Previous studies of China's national and provincial essential drug lists and the zero markup policy have instead focused largely on the policy's intended effects. [20][21][22][23][24][25][26][27][28][29][30] These studies have reported varying and sometimes conflicting results, perhaps in part because of their reliance on cross-sectional and before-after study designs. Some report reductions in clinicians' income under the policy.…”
mentioning
confidence: 99%
“…Results in Tables 2-4 are first listed for programs targeted at children and then for other programs. Seven out of 13 papers are concerned with health insurance expansion for the general population in Burkina Faso (Fink et al, 2013), China (Wagstaff & Yu, 2007;Chen & Jin, 2012), Colombia (Giedion & Uribe, 2009;Miller et al, 2013), Rwanda (Lu et al, 2012), and Thailand (Gruber et al, 2014). Five papers cover health insurance programs targeted at children in the Philippines (Kraft et al, 2009;Quimbo et al, 2011) and Vietnam (Wagstaff & Pradhan, 2005;Nguyen & Wang, 2013;Guindon, 2014;Palmer et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that one paper (Guindon, 2014) deals with both a program targeted at children and a program for a larger population. 4 With respect to methodology, three articles used a difference-in-difference design (Nguyen & Wang, 2013;Gruber et al, 2014;Guindon, 2014), one paper used propensity score matching (Lu et al, 2012), four papers used difference-indifference and propensity score matching combined (Wagstaff & Pradhan, 2005;Wagstaff & Yu, 2007;Giedion & Uribe, 2009;Chen & Jin, 2012), three papers used a randomised controlled trial (Kraft et al, 2009;Quimbo et al, 2011;Fink et al, 2013), and two papers used a regression discontinuity design (Miller et al, 2013;Palmer et al, 2015). Note: * One study (Guindon, 2014) covers a program targeted at children and another program that is not targeted, hence the number of studies here sums to 14.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation